2014
DOI: 10.5152/akd.2014.5488
|View full text |Cite
|
Sign up to set email alerts
|

Relation of ABO blood groups to coronary lesion complexity in patients with stable coronary artery disease

Abstract: Author`s ReplyTo the Editor,We would like to thank the authors of the letter for their interest and criticism about our study published in February issue of The Anatolian Journal of Cardiology 2014; 14: 55-60 (1). The relation between ABO blood groups and coronary artery disease is known for many years. But, there are no adequate information about the causes of relation between ABO blood groups and coronary artery diseases. In our study, we tried to discuss the relation between ABO blood groups and the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent metastudy also confirmed that non-O blood group appears to be an independent risk factor for CAD and myocardial infarction, and non-O blood group was associated with a statistically significant 14% increase in CAD incidence relative to O blood group [ 4 ]. Moreover, clinical data on the association of ABO blood groups with severity of CAD have shown that ABO blood groups were significantly related to severity of CAD, non-O blood group was found to be the independent predictors of high SYNTAX score [ 5 ], and O blood group was shown as a protective factor of high Gensini score [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent metastudy also confirmed that non-O blood group appears to be an independent risk factor for CAD and myocardial infarction, and non-O blood group was associated with a statistically significant 14% increase in CAD incidence relative to O blood group [ 4 ]. Moreover, clinical data on the association of ABO blood groups with severity of CAD have shown that ABO blood groups were significantly related to severity of CAD, non-O blood group was found to be the independent predictors of high SYNTAX score [ 5 ], and O blood group was shown as a protective factor of high Gensini score [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conflicting results in the literature. In one study, no relationship between ABO blood groups and CAD was shown [19]. In addition, another study showed that ABO blood groups dsitributions were similar in patient with CAD [20].…”
Section: Discussionmentioning
confidence: 95%